Ultraviolet Absorption Cross-Sections of Ammonia at Elevated Temperatures for Nonintrusive Quantitative Detection in Combustion Environments - Weng, Wubin; Li, Shen; Aldén, Marcus; Li, Zhongshan (Applied spectroscopy, 2021)
Ammonia (NH3) is regarded as an important nitrogen oxides (NOx) precursor and also as an effective reductant for NOx removal in energy utilization through combustion, and it has recently become an attractive non-carbon alternative fuel. To have a better understanding of thermochemical properties of NH3, accurate in situ detection of NH3 in high temperature environments is desirable. Ultraviolet (UV) absorption spectroscopy is a feasible technique. To achieve quantitative measurements, spectrally resolved UV absorption cross-sections of NH3 in hot gas environments at different temperatures from 295 K to 590 K were experimentally measured for the first time. Based on the experimental results, vibrational constants of NH3 were determined and used for the calculation of the absorption cross-section of NH3 at high temperatures above 590 K using the PGOPHER software. The investigated UV spectra covered the range of wavelengths from 190 nm to 230 nm, where spectral structures of the A ∼